Integración de organizaciones y empresas al territorio por medio de innovaciones sociales (Integration of organizations and companies at territories through social innovations) - Portales, Luis (Facultad de Contaduría Pública y Administración, 2015)
Abstract. Territory is a concept that has been approached from different scopes of social sciences. As a result of its study, currently is understand as a multidimensional and complex form, where not only take into consideration the geographical aspect and availability of resources, but also includes a relational and dynamic aspect. Consequence of this view it can be used as a framework to analyze the different connections that social actors presents between them, and the causes, implications and effects they have on the territory where they operate. The aim of this paper is to present how different actors have been integrated into the territory as a result of the breakdown in social roles that state, civil society and companies traditionally had been doing. These schemes of collaboration and integration can be understood as social innovations that generate socioeconomic processes aimed to improving living conditions for all inhabitants. The analysis is a framework that serves as the basis for the study of social innovations that occur most frequently in the current context.